Customer Satisfaction Memediasi Pengaruh Brand Image dan Perceive Value Terhadap Niat Beli Kembali (Studi Kasus Konsumen Vape di Kota Semarang) - Saputra, Adhitya Bagus; Basiya, Basiya (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The purpose of this study was to determine whether customer satisfaction mediates the influence of brand image and perceived value on consumer purchase intention. The method used in this study was quantitative, with primary data. Because the exact number of population members was unknown, the sample size was calculated using the Cochran formula, with a sample size of 96 people. The sampling technique used was purposive sampling. The data analysis technique used was the Sobel Test. The results of this study showed that brand image has a positive effect on customer satisfaction. Perceived value has a positive effect on customer satisfaction. Brand image has a positive effect on consumer purchase intention. Perceived value has a positive effect on consumer purchase intention. Customer satisfaction has a positive effect on consumer purchase intention. Customer satisfaction did not mediate the effect of brand image on consumer purchase intention. Customer satisfaction did mediate the effect of perceived value on consumer purchase intention.